He Effect of Employee's Distribution and Authority on Employee Performance at PT. Huki Branch Medan - Teddy Pribadi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Effect of Consumer Perception and Marketing Strategy on Increasing Sales of Kokita in Medan